Immune modulation in inflammatory bowel disease: therapeutic promise of baicalein - Wang, Yang; Zeng, Luyao (Frontiers in Pharmacology, 2025)
Inflammatory bowel disease (IBD) remains a major global health burden, driven by a multifaceted pathogenesis that includes immune dysregulation, epithelial barrier disruption, oxidative stress, and gut microbiota imbalance. Addressing these interconnected processes requires multi-targeted therapeutic strategies that go beyond conventional single-pathway interventions. Baicalein, a key flavonoid derived from Scutellaria baicalensis (Huang Qin), has emerged as a promising candidate due to its broad-spectrum pharmacological properties. This review synthesizes current advances in understanding how baicalein exerts therapeutic effects against IBD through an integrated network of mechanisms. These include potent suppression of inflammatory signaling and oxidative stress, restoration of epithelial integrity via modulation of tight junction proteins and the MLCK/p-MLC2 pathway, and reprogramming of dysregulated immune circuits by rebalancing T-cell subsets and macrophage polarization. In addition, baicalein mitigates pathological cell death pathways such as ferroptosis and pyroptosis and orchestrates beneficial shifts in the gut microbiota–metabolite axis. By bridging classical anti-inflammatory mechanisms with emerging immunoregulatory and microbiome-targeted insights, this review highlights baicalein as a potential multi-dimensional therapeutic strategy for IBD and outlines future directions for its clinical translation.